2020
DOI: 10.1007/s00270-020-02658-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Vertebral Body Augmentation System in the Treatment of Patients with Symptomatic Vertebral Body Fractures

Abstract: Purpose To evaluate the safety and efficacy of a novel augmentation implant in the treatment of patients with symptomatic vertebral body fractures. Materials and Methods Thirty consecutive patients (seven males and 23 females), mean age of 70 years (range 56 to 89) with osteoporotic fractures and/or low-energy trauma fractures (osteoporosis confirmed by CT), were enrolled in an IRB-approved prospective study. The type of fracture was classified according to the Magerl classification. The patients were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A: PMMA bone cement (PBC) : Commercial PBC (Mendec® Spine 1230, Tecres S.p.A., Italy), which is a product for vertebroplasty and had been used in the study of PBC optimization [ 47 , 48 ],was used as the control in the present study. According to the manufacturer's instruction, a package of Mendec® Spine consists of a solid phase (20 ​g) and a liquid phase (10 ​mL).…”
Section: Methodsmentioning
confidence: 99%
“…A: PMMA bone cement (PBC) : Commercial PBC (Mendec® Spine 1230, Tecres S.p.A., Italy), which is a product for vertebroplasty and had been used in the study of PBC optimization [ 47 , 48 ],was used as the control in the present study. According to the manufacturer's instruction, a package of Mendec® Spine consists of a solid phase (20 ​g) and a liquid phase (10 ​mL).…”
Section: Methodsmentioning
confidence: 99%
“…A new type of spinal kyphoplasty has been described using the Tektona® device and compared to the balloon, for the moment only in spine and cadavers [9,10]. The advantage of the Tektona® system lies in its unidirectional exible lamella which can be oriented several times to obtain a better control of the plateau uplifting (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The rst one, by Krüger et al was a cadaveric study, comparing the Tektona® to a standard balloon kyphoplasty concluded to promising results [14]. Secondly, Marcia et al described a cohort of 30 patients, with encouraging results in terms of clinical scores and vertebral body height (VBH) restoration but only on a osteoporotic population [15]. Is the Tektona reliable in terms of sagittal correction on acute vertebral fractures?…”
Section: Introductionmentioning
confidence: 99%